A critical role of Src family kinase in SDF-1/CXCR4-mediated bone-marrow progenitor cell recruitment to the ischemic heart. (April 2015) - Cheng, Min; Huang, Kai; Zhou, Junlan; Yan, Dewen; Tang, Yao-Liang; Zhao, Ting C.; Miller, Richard J.; Kishore, Raj; Losordo, Douglas W.; Qin, Gangjian
Abstract: The G protein-coupled receptor CXCR4 and its ligand stromal-cell derived factor 1 (SDF-1) play a crucial role in directing progenitor cell (PC) homing to ischemic tissue. The Src family protein kinases (SFK) can be activated by, and serve as effectors of, G proteins. In this study we sought to determine whether SFK play a role in SDF-1/CXCR4-mediated PC homing. First, we investigated whether SDF-1/CXCR4 signaling activates SFK. Bone-marrow mononuclear cells (BM MNCs) were isolated from WT and BM-specific CXCR4-KO mice and treated with SDF-1 and/or CXCR4 antagonist AMD3100. SDF-1 treatment rapidly induced phosphorylation (activation) of hematopoietic Src (i.e., Lyn, Fgr, and Hck) in WT cells but not in AMD3100-treated cells or CXCR4-KO cells. Then, we investigated whether SFK are involved in SDF-1/CXCR4-mediated PC chemotaxis. In a combined chemotaxis and endothelial-progenitor-cell (EPC) colony assay, Src inhibitor SU6656 dose-dependently inhibited the SDF-1-induced migration of colony-forming EPCs. Next, we investigated whether SFK play a role in SDF-1/CXCR4-mediated BM PC homing to the ischemic heart. BM MNCs from CXCR4BAC :eGFP reporter mice were i.v. injected into WT and SDF-1BAC :SDF1-RFP transgenic mice following surgically-induced myocardial infarction (MI). eGFP + MNCs and eGFP + c-kit + PCs that were recruited in the infarct border zone in SDF-1BAC :SDF1-RFP recipients were significantly more than that in WT recipients. Treatments of mice with SU6656 significantly reduced eGFP + and eGFP + c-kit + cell recruitment in both WT and SDF-1BAC :RFP recipients and abrogated the difference between the two groups. Remarkably, PCs isolated from BM-specific C-terminal Src kinase (CSK)-KO (Src activated) mice were recruited more efficiently than PCs from WT PCs in the WT recipients. In conclusion, SFK are activated by SDF-1/CXCR4 signaling and play an essential role in SDF-1/CXCR4-mediated BM PC chemotactic response and ischemic cardiac recruitment. Highlights: The SDF-1/CXCR4 axis crucially directs progenitor cell (PC) homing to ischemic tissue. SDF-1/CXCR4 signaling activates Src family kinases (SFK) in the bone marrow (BM) PCs. Inhibition of SFK impairs SDF-1-induced migration of BM PCs. SFK are essential for SDF-1-mediated recruitment of BM PCs to the ischemic myocardium.